Religion As Subaltern Agency - Gregory Ajima Onah; Thomas Eneji Ogar; Ibiang O. Okoi (Vox Dei: Jurnal Teologi dan Pastoral, 2024)
This study examines the role of religion in facilitating the liberation of marginalized and oppressed groups, sometimes referred to as the subaltern. The word "subaltern," which connotes inferiority, was used by Antonio Gramsci to describe social groupings that are subjugated by the dominant ruling class. The subaltern classes primarily include individuals such as peasants, laborers, and other marginalized groups who have been systematically excluded from positions of hegemonic authority. This exclusion may be attributed to the historical focus on governments and dominant social groupings within the narrative of power dynamics. Gramsci posited that the historical trajectory of the subaltern classes has a comparable level of intricacy to that of the dominant classes. This work argues that, from Gramsci's perspective, the historical narrative of subaltern social groups is inherently fragmented and characterized by episodic occurrences. This is mostly due to the constant influence exerted by dominant groups, even in instances of rebellion. This work submits that it is evident that individuals belonging to this group possess limited opportunities to exercise agency over their own portrayal and encounter restricted access to cultural and social establishments. The cessation of subordination can only be achieved through a lasting triumph, not instantaneously.